Estimation of an Optimal Portfolio Using the Constant Correlation Model: An Empirical Study on IDX Bisnis-27 Stocks - Jehan Rizky Faustina Hartono; Anastasia Audrey Wijaya; Sukono (International Journal of Quantitative Research and Modeling, 2025)
Portfolio optimization is an essential aspect of investment decision-making, as investors aim to achieve an optimal trade-off between expected return and risk. However, the traditional Markowitz portfolio model requires the estimation of a large variance–covariance matrix, which becomes computationally complex as the number of assets increases. To address this limitation, this study applies the Constant Correlation Model (CCM), which simplifies portfolio construction by assuming a constant correlation among asset returns. This study aims to estimate an optimal stock portfolio using the CCM approach based on stocks included in the IDX Bisnis-27 index, representing companies with strong business fundamentals listed on the Indonesia Stock Exchange. The data consist of daily closing prices of 28 stocks for the period from January to December 2023. The analysis involves calculating stock returns, expected returns, standard deviations, Excess Return to Standard Deviation (ERS), constant correlation, and the cut-off rate (C*). The results show that the average constant correlation among the selected stocks indicates a moderate level of interdependence, suggesting that diversification benefits still exist. Based on the CCM selection criteria, only one stock, ANTM, has an ERS value exceeding the cut-off rate and is therefore included in the optimal portfolio with a weight of 100%. These findings indicate that ANTM exhibits the strongest risk-adjusted performance among IDX Bisnis-27 stocks during the observation period. This study provides practical insights for investors in constructing optimal portfolios using simplified correlation assumptions in emerging markets.